Extreme lifespan extension in tapeworm-infected ant workers. Issue 5 (19th May 2021) - Beros, Sara; Lenhart, Anna; Scharf, Inon; Negroni, Matteo Antoine; Menzel, Florian; Foitzik, Susanne
Abstract : Social insects are hosts of diverse parasites, but the influence of these parasites on phenotypic host traits is not yet well understood. Here, we tracked the survival of tapeworm-infected ant workers, their uninfected nest-mates and of ants from unparasitized colonies. Our multi-year study on the ant Temnothorax nylanderi, the intermediate host of the tapeworm Anomotaenia brevis, revealed a prolonged lifespan of infected workers compared with their uninfected peers. Intriguingly, their survival over 3 years did not differ from those of (uninfected) queens, whose lifespan can reach two decades. By contrast, uninfected workers from parasitized colonies suffered from increased mortality compared with uninfected workers from unparasitized colonies. Infected workers exhibited a metabolic rate and lipid content similar to young workers in this species, and they received more social care than uninfected workers and queens in their colonies. This increased attention could be mediated by their deviant chemical profile, which we determined to elicit more interest from uninfected nest-mates in a separate experiment. In conclusion, our study demonstrates an extreme lifespan extension in a social host following tapeworm infection, which appears to enable host workers to retain traits typical for young workers.